Spiritual issues in mental health care - Dombeck, Mary (Journal of religion and health, 1987)
Religious and spiritual issues in mental health are explored in the context of four conceptual models: the medical, the nursing, the humanistic, and the pastoral. This is done by looking at each model in terms of content, diagnostic focus, language and treatment goals, and primary qualities in the health provider.The models are illustrated by case studies gathered from a multidisciplinary setting. The discovery that each model can incorporate the religious and spiritual dimension in mental health care, but that each model does this in distinctive ways, is a key point.